Revitalisasi Seni Jaran Kepang Kabupaten Temanggung Jawa Tengah - Mutiarasari, Kartika; Suwandi, Tuteng (Jurnal Pendidikan Tari, 2022)
Temanggung Regency is famous for the performance art of Kuda Lumping, especially after experiencing developments in 1972, namely by rearranging motion, accompaniment, make-up, clothing, and other supporting elements, and structuring motion. So that in that era this art was very well known and became the pride of the Temanggung people for being part of the opening ceremony of the Taman Mini Indonesia Indah in 1975. Since the late 1990s this art has experienced developments carried out by each group by incorporating elements of other regional cultures. even elements of western culture in the show. It is feared that the younger generation does not know the original form of the Kuda Lumping dance movement. This study uses a qualitative approach. Data collected through observation, interviews, observations, and active participation. The data obtained in the form of oral and written data as well as recordings. The data were analyzed using a flow model, because among the activities of collecting, reducing, presenting in the form of conclusions, they were carried out in an